TRACKING PERFORMANCE AND DISTURBANCE REJECTION OF PNEUMATIC ACTUATOR SYSTEM - Syed Salim , Syed Najib; Rahmat, Mohd Fua'ad; Mohd Faudzi, Ahmad 'athif; Ismail, Zool H.; Sunar, Noorhazirah; Sharatul Izah, Sharatul Izah (2013)
This paper investigates several control strategies that potential to perform well in regulating and tracking set point of pneumatic actuator system and able to reject disturbance. The system consists of 5-port proportional valve with the dead-band flow and double rod cylinders that exhibit significant friction. Two control strategies of PID and NPID controllers with four different configurations with and without dead-zone compensators (DZC) are simulated. Three different input signals including step, sinusoidal and random waveforms are used to evaluate the performance of the proposed techniques. The effectiveness of NPID+DZC has been successfully demonstrated and proved through simulation and experimental studies.